1983
DOI: 10.1111/j.1600-0765.1983.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent polysaccharide cohesion among Actinomyces viscosus and Actinomyces naeslundii fresh isolates of human origin

Abstract: Dextran‐mediated agglutination has been both proposed and opposed as a mechanism for cohesive interactions between Actinomyces viscosus and streptococci in dental plaques. In their Studies, opponents of this mechanism used laboratory strains subcultured in vitro for unknown periods, whereas its proponents had previously shown that laboratory passage of Actinomyces strains weakened this trait. To clarify this issue, eighty‐eight strains of A. viscosus and Actinomyces naeslundii freshly isolated from the human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A. viscosus strain 262 and A. naeslundii strain 151 were originally isolated from the plaques over root surface caries lesions, whereas A. viscosus strain 251 and A. naeslundii strain 226 were ori ginally isolated from the plaques over intact root surfaces [Komiyama et al, 1986]. These strains have been kept in vials containing serum-coated glass beads at -70°C [Ellen et al, 1983], and have never been subcultured. Each strain was grown anaerobically (10% CO;, 10% H,.…”
Section: Organisms and Cultural Conditionsmentioning
confidence: 99%
“…A. viscosus strain 262 and A. naeslundii strain 151 were originally isolated from the plaques over root surface caries lesions, whereas A. viscosus strain 251 and A. naeslundii strain 226 were ori ginally isolated from the plaques over intact root surfaces [Komiyama et al, 1986]. These strains have been kept in vials containing serum-coated glass beads at -70°C [Ellen et al, 1983], and have never been subcultured. Each strain was grown anaerobically (10% CO;, 10% H,.…”
Section: Organisms and Cultural Conditionsmentioning
confidence: 99%
“…In S. mutans, however, it has been reported that this property can be lost during laboratory passages. The above results did not agree with those of McBride and Bourgeau (1975) who reported that all A. viscosus strains, including human isolates, are equally sensitive to dextran-induced agglutination, but supported the finding that freshly isolated Actinomyces strains of human origin exhibited no significant agglutination in buffered dextran T2000 (Eiien, Fillery & Seckington 1983). Furthermore, Cisar, Kolenbrander and Mclntire (1979) have reported that rodent but not human strains of A. viscosus are agglutinated by dextran.…”
Section: Resultsmentioning
confidence: 66%
“…The broth culture was then transferred into several vials containing serum-coated glass beads and immediately frozen at -700C (Ellen et al, 1983). These frozen beads were always used to inoculate growth medium for each experiment, thus avoiding further laboratory passage of the original isolate.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is little information on these aspects of oral Actinomyces, particularly fresh clinical isolates of this species. There has been some evidence to suggest that the physiology of laboratory strains may not resemble that of freshly isolated strains and may not be relevant to the in vivo state (Hamilton and Bowden, 1982;Ellen et al, 1983;Vadeboncoeur and Trahan, 1983). The purpose of the present study was to investigate relative glycogen synthetic abilities of A. viscosus and A. naeslundii freshly isolated from the dental plaque over intact root surfaces and over root surface caries lesions.…”
Section: Introductionmentioning
confidence: 97%